Gibberellin Induced Transcriptome Profiles Reveal Gene Regulation of Loquat Flowering - Jiang, Yuanyuan; Liu, Yicun; Gao, Yongshun; Peng, Jiangrong; Su, Wenbing; Yuan, Yuan; Yang, Xianghui; Zhao, Chongbin; Wang, Man; Lin, Shunquan; Peng, Ze; Xie, Fangfang (Frontiers in Genetics, 2021)
Flowering is an integral part of the life cycle of flowering plants, which is essential for plant survival and crop production. Most woody fruit trees such as apples and pears bloom in spring, but loquat blooms in autumn and winter. Gibberellin (GA) plays a key role in the regulation of plant flower formation. In this study, we sprayed loquat plants with exogenous GA3, which resulted in vigorous vegetative growth rather than floral bud formation. We then performed a comprehensive RNA-seq analysis on GA3-treated and control-treated leaves and buds over three time periods to observe the effects of exogenous GA3 application on floral initiation and development. The results showed that 111 differentially expressed genes (DEGs) and 563 DEGs were down-regulated, and 151 DEGs and 506 DEGs were up-regulated in buds and leaves, respectively, upon treatment with GA3. Among those that are homologs of the DELLA-mediated GA signal pathway genes, some may be involved in the positive regulation of flower development, including EjWRKY75, EjFT, EjSOC1, EjAGL24, EjSPL, EjLFY, EjFUL, and EjAP1; while some may be involved in the negative regulation of flower development, including EjDELLA, EjMYC3, EjWRKY12, and EjWRKY13. Finally, by analyzing the co-expression of DEGs and key floral genes EjSOC1s, EjLFYs, EjFULs, EjAP1s, 330 candidate genes that may be involved in the regulation of loquat flowering were screened. These genes belong to 74 gene families, including Cyclin_C, Histone, Kinesin, Lipase_GDSL, MYB, P450, Pkinase, Tubulin, and ZF-HD_dimer gene families. These findings provide new insights into the regulation mechanism of loquat flowering.